Household Food Security and Individual Dietary Diversity as Determinants of Stunting: Evidence from a Primary Healthcare Center - Sarah Melati Davidson; Hijrah Asikin; Thresia Dewi Kartini (Journal of Health and Nutrition Research, 2026)
Stunting in children remains a priority nutrition problem in Indonesia. Household food security and individual dietary diversity are presumed to play important roles in the nutritional status of children under five. This study aims to determine the association between individual dietary diversity and household food security with the nutritional status of children aged 12–59 months in the Tamalanrea Health Center area, Makassar. This quantitative, cross-sectional study involved 81 children aged 12-59 months, selected using a purposive sampling technique. Data collection included measurement of nutritional status using the height-for-age indicator, household food security using the Household Food Insecurity Access Scale (HFIAS), and individual dietary diversity using the Individual Dietary Diversity Score (IDDS). Data analysis was performed univariately and bivariately using the chi-square test. The prevalence of stunting was 28.4% among the total research subjects. Household food security was significantly associated with children's nutritional status, as indicated by H/A (p=0.019), with children from food-insecure households having a 3.4 times greater risk of stunting (OR=3.429; 95% CI: 1.242-9.464). Conversely, individual dietary diversity did not show a significant relationship with children's nutritional status (p=0.424). Consumption of legumes and nuts was very low (6.17%), and consumption of vitamin A-rich fruits and vegetables was below 50%. Household food security is a more determinative factor in children's nutritional status than individual dietary diversity. Stunting prevention interventions need to focus on improving household economic access to food through multisectoral approaches